2004
DOI: 10.1614/wt02-180
|View full text |Cite
|
Sign up to set email alerts
|

Orchard Floor Management Influence on Summer Annual Weeds and Young Peach Tree Performance

Abstract: This study compared the effect of weed control and orchard floor management (OFMA) options including organic mulch on summer annual weed interference in a newly established peach orchard. Weed interference where no preemergence (PRE) herbicides were applied, including vole damage, caused 29% peach tree mortality, reduced tree trunk cross-sectional area (TCSA) 62% by the fourth year of orchard establishment, and reduced fruit yield and fruit number in 1999 by 73 and 75%, respectively, but had no effect on fruit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 17 publications
1
14
0
1
Order By: Relevance
“…Parker et al (1993) demonstrated that peach tree growth, expressed as change in trunk cross-sectional area (TCSA), was greater in a weed-free environment than a weedy environment. Other research documented that weed pressure in a young peach orchard reduced TCSA compared to a weed-free environment (Belding et al, 2004). Competition was also detected between apple trees and slow growing living mulches as compared to a weed-free control (Hoagland et al, 2008).…”
mentioning
confidence: 92%
“…Parker et al (1993) demonstrated that peach tree growth, expressed as change in trunk cross-sectional area (TCSA), was greater in a weed-free environment than a weedy environment. Other research documented that weed pressure in a young peach orchard reduced TCSA compared to a weed-free environment (Belding et al, 2004). Competition was also detected between apple trees and slow growing living mulches as compared to a weed-free control (Hoagland et al, 2008).…”
mentioning
confidence: 92%
“…However, any vegetation growing in plant rows and interrows of orchards is a strong competitor for water, nutrients, and yield (Wright et al, 2003;Belding et al, 2004). Previous studies have indicated that mowing the vegetation in the interrow and applying herbicides to the plant row are the best practices for sustainable soil management in orchards (Hogue and Neilsen, 1987;Lipecki and Berbeć, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Cover crops can provide effective weed suppression for such cropping systems. Winter annual cover crops have been successfully incorporated into crop rotations and are most widely used to date to control weeds in various crops (Belding et al 2004;Brennan and Smith 2005;Buhler et al 1996;Hooker et al 1997).…”
Section: Discussionmentioning
confidence: 99%